The Efficacy of Vitamin D Supplementation to Reduce Urticaria: Systematic Review - Devi, Jean Budi Pratista; Rohmawati, Indah (Writing Center IMERI FMUI, 2023)
Urticaria is a condition of skin disorders. Based on the duration of symptoms, chronic urticaria occurs > 6 weeks. Chronic urticaria is caused by endogenous factors unrelated to an external physical stimuli. Vitamin D is an immunoregulatory hormone that activates innate and adaptive immune responses. A literature search was conducted in PubMed, ScienceDirect, SpringerLink, and ProQuest with a publication year limit of 2011–2023. The keywords used were